Characterisation of waste manganese carbonate for biooxidation effluent neutralisation - Gordon, J. J. K.; Asiam, E. K. (University of Mines and Technology, 2017)
The conventional chemical used in the neutralisation of biooxidation effluents is lime. The search for cheaper and readily available alternative reagents has been the motivation for a number of researches. This paper considered the characterisation and utilisation of Waste Manganese Carbonate (WMC) (waste-bearing manganese carbonate material) from Ghana Manganese Company in Ghana as a neutralising agent for biooxidation effluents. The WMC is composed of manganese carbonate (76.6%), dolomite (7.1%), muscovite (8.5%), quartz (6.5%), todorokite (0.3%) and the amorphous content was 1.0%. The elemental Mn content was approximately 28.26%. The Bond Index was 13.52 kWh/t, and the particle size distribution gave D50 as 5.89 μm. The isoelectric point (iep) of the WMC dispersed in MilliQ water occurred at ~pH 8.5, and the powder specific surface area measured was 6.12 m2/g. WMC was used to neutralise biooxidation effluent with arsenic concentration of 1276 mg/L at pH 1.85 and 27 oC and it was able to deprotonate the effluent from pH 1.85 to 5.5 in 120 min depending on solid loading. Arsenic sequestration increased with increasing WMC concentration with residual arsenic concentration in solution ranging between 0.78 and 1.11 mg/L at pH 7.0. Surface area of the WMC precipitates was 12.62 m2/g and the corresponding D50 values at pH 4.5 and 7.0 were respectively 5.89 μm and 10.35 μm. Mobile arsenic extracted from the precipitates averaged 4.135 mg/L at pH 7.0 and 1.594 mg/L at pH 7.4 as against the EPA maximum allowable concentration of 5.0 mg/L.
Keywords: Biooxidation Effluent Neutralisation; Waste Manganese Carbonate; Characterisation; Work Index